Tactical Military Leader Requisite Complexity: Toward a Referent Structure. - Hannah ST; Jennings PL; Nobel OB (Military Psychology)
The U.S. Army has focused on developing leader competencies in order to promote adaptability for asymmetric warfare. Expanding leader adaptive capacity, however, requires integrating competencies with deeper knowledge structures and leader identity. We conduct a three-stage exploratory study using semistructured interviews and three separate samples of experienced combat leaders to assess the organization of tactical leader functional roles. We identify the breadth of roles, tasks, skills, and attributes representative of expert tactical military leaders. We hope to take a first step in circumscribing the requisite cognitive and behavioral complexity required of tactical leaders and thereby provide a referent structure for future research on what constitutes requisite complexity for tactical military leaders.